Numerical analysis and optimization of the performance of CO2-Plume Geothermal (CPG) production wells and implications for electric power generation. (January 2022) - Ezekiel, Justin; Adams, Benjamin M.; Saar, Martin O.; Ebigbo, Anozie
Highlights: A coupled flow and power model is set up to optimize the flowrate of CPG wells. The optimal flowrate maximizes power output and minimizes reservoir pressure drawdown. We show that water accumulation in the production well is avoidable. The minimal superficial CO2 velocity can be a design parameter for a CPG system. An explanation is given on why the cranfield CO2 thermosiphon field test failed. Abstract: CO2 -Plume Geothermal (CPG) power plants can produce heat and/or electric power. One of the most important parameters for the design of a CPG system is the CO2 mass flowrate. Firstly, the flowrate determines the power generated. Secondly, the flowrate has a significant effect on the fluid pressure drawdown in the geologic reservoir at the production well inlet. This pressure drawdown is important because it can lead to water flow in the reservoir towards and into the borehole. Thirdly, the CO2 flowrate directly affects the two-phase (CO2 and water) flow regime within the production well. An annular flow regime, dominated by the flow of the CO2 phase in the well, is favorable to increase CPG efficiency. Thus, flowrate optimizations of CPG systems need to honor all of the above processes. We investigate the effects of various operational parameters (maximum flowrate, admissible reservoir-pressure drawdown, borehole diameter) and reservoir parameters (permeability anisotropy and relative permeability curves) on the CO2 and water flow regime in the production well and on the power generation of a CPG system. We use a numerical modeling approach that couples the reservoir processes with the well and power plant systems. Our results show that water accumulation in the CPG vertical production well can occur. However, with proper CPG system design, it is possible to prevent such water accumulation in the production well and to maximize CPG electric power output.